Empowering Communities through Ecobrick-Based Environmental Literacy for Sustainable Plastic Waste Management - Anti Isnaningsih; Wafa Aerin; Iys Nur Handayani; Rifangi Munir; Umi Ma'rifatul; Etha Kurnia Widi; Vera Yuliana; Asyitul Khotimah; Farid muadzin; Ramaditya Sindu; Rizki Imam Khudori; Mukhtar Nazir (Al-Qalam Institute, 2026)
This community service program aimed to empower communities through ecobrick-based environmental literacy as an innovative approach to plastic waste management. The program was implemented using a participatory approach, with several stages: observation, problem identification, socialization, training, and continuous mentoring to encourage active community participation. The activities focused on increasing public awareness of environmental issues and on promoting practical solutions to reduce plastic waste through ecobrick production. The results showed that community members, especially women's groups and youth organizations, were able to transform plastic waste into ecobricks that were further utilized as functional products, such as plant pots and simple waste bins. In addition, the program successfully improved community understanding of environmental cleanliness, waste reduction, and the importance of sustainable environmental practices. The implications of this program suggest that ecobrick-based environmental literacy can be an effective strategy for strengthening community participation, encouraging environmentally responsible behavior, and supporting sustainable plastic waste management at the local level. Furthermore, the program fostered long-term environmental awareness and collective responsibility within the community.